Cash Waqf Linked Sukuk: Innovative Financing for Educational Infrastructure - Mihajat, Muhammad Iman Sastra; Hawariyuni, Weni Hawariyuni (UPT Publikasi Ilmiah UNISBA, 2025)
The aim of this paper is to examine the role of Cash Waqf Linked Sukuk (CWLS) as an innovative financing for building educational infrastructure in Indonesia. The fact that educational infrastructure and facilities are still scarce in educational buildings is the driving force for this research. The research based on a qualitative methodology using the data from scientific journals and paper in the field of Cash Waqf, including CWLS. CWLS shall consists of 3 instruments, namely waqf sukuk, government retail waqf sukuk and Waqf project. Currently the coupons from waqf sukuk have been channeled to finance the construction of the retina center and glaucoma center at the hospital. The country needs to explore the use of cash waqf from CWLS for other programs such as building educational infrastructure by involving Islamic bank to finance the program, that might benefit citizens more in the future. This study demonstrates that it is feasible to use the financing raised by the CWLS to construct infrastructure and educational facilities that will improve student and teacher/lecturer performance.